Common variants in SOX-2 and congenital cataract genes contribute to age-related nuclear cataract - Yonova-Doing, Ekaterina; Zhao, Wanting; Igo, Robert P.; Wang, Chaolong; Sundaresan, Periasamy; Lee, Kristine E.; Jun, Gyungah R.; Alves, Alexessander Couto; Chai, Xiaoran; Chan, Anita S. Y.; Lee, Mei Chin; Fong, Allan; et al. (Communications biology, 2020)
Nuclear cataract is the most common type of age-related cataract and a leading cause of blindness worldwide. Age-related nuclear cataract is heritable (h2 = 0.48), but little is known about specific genetic factors underlying this condition. Here we report findings from the largest to date multi-ethnic meta-analysis of genome-wide association studies (discovery cohort N = 14,151 and replication N = 5299) of the International Cataract Genetics Consortium. We confirmed the known genetic association of CRYAA (rs7278468, P = 2.8 × 10−16) with nuclear cataract and identified five new loci associated with this disease: SOX2-OT (rs9842371, P = 1.7 × 10−19), TMPRSS5 (rs4936279, P = 2.5 × 10−10), LINC01412 (rs16823886, P = 1.3 × 10−9), GLTSCR1 (rs1005911, P = 9.8 × 10−9), and COMMD1 (rs62149908, P = 1.2 × 10−8). The results suggest a strong link of age-related nuclear cataract with congenital cataract and eye development genes, and the importance of common genetic variants in maintaining crystalline lens integrity in the aging eye.